2021
DOI: 10.3389/fpsyg.2021.627669
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Collective Cultural Attributes on Covid-19-Related Public Health Outcomes

Abstract: Infections and deaths associated with COVID-19 show a high degree of heterogeneity across different populations. A thorough understanding of population-level predictors of such outcomes is crucial for devising better-targeted and more appropriate public health preparedness measures. While demographic, economic, and health-system capacity have featured prominently in recent work, cultural, and behavioral characteristics have largely been overlooked. However, cultural differences shape both the public policy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 78 publications
1
30
0
1
Order By: Relevance
“…Thus, we argue that the cultural dimensions that characterize nations influence both the dissemination and the severity of the COVID-19 disease in their populations because culture fundamentally shapes how people respond to crises such as the COVID-19 (Lu et al, 2021). According to Erman and Medeiros (2021) during the initial period of a pandemic, policy makers should more explicitly consider the cultural attributes of a society along with other important parameters such as demographic characteristics and healthcare system constraints in order to develop more tailored and effective policy responses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we argue that the cultural dimensions that characterize nations influence both the dissemination and the severity of the COVID-19 disease in their populations because culture fundamentally shapes how people respond to crises such as the COVID-19 (Lu et al, 2021). According to Erman and Medeiros (2021) during the initial period of a pandemic, policy makers should more explicitly consider the cultural attributes of a society along with other important parameters such as demographic characteristics and healthcare system constraints in order to develop more tailored and effective policy responses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in countries with low uncertainty avoidance, people are very interested in politics and go to protests because they are tools of change. However, it was found that countries with high uncertainty avoidance had lower rates of COVID-19 than those with low uncertainty avoidance [20].…”
Section: Masculinity or Tough Versus Femininity Or Tender (Mas)mentioning
confidence: 93%
“…COVID-19 surveillance during the week of April 12-25, 2021, indicates that with the exception of Bangladesh and Pakistan, South Asia is experiencing an alarming outbreak of COVID-19. First, while there are many similarities in terms of development, the environment, and population structure, South Asian countries are heterogeneous in terms of their culture, economies, and susceptibility to the COVID-19 pandemic [49]. Second, migrant workers are central to disease control in South Asia, considering the large number of migrants in most South Asian countries [50].…”
Section: Principal Findingsmentioning
confidence: 99%